Immigrants’ Experiences of Becoming Bilingual (A Case Study of German and Indonesian bilinguals Living in Australia) - Sabarniati Sabarniati; Naria Fitriani (Lembaga Pengembangan Kinerja Dosen, 2023)
As an immigrant living in Australia, having proficiency in English is a must. With the background of language includes several mother tongues, bilingualism is directly acquired since living in the English country. Dealing with this case, this study aims at investigating diverse Australian immigrants’ experiences of becoming bilingual and underlines their implication for EFL (English as a Foreign Language) study. Two participants; German and Indonesian immigrants living in Australia for about 20 years taking apart during this study. Qualitatively, the immigrants were interviewed then the data were analyzed. The results found that both of them have some shared and distinctive multilingual experiences. In addition, it indicated that they were in different phases of their bilingual development.